2000
DOI: 10.1111/1467-9957.00196
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Equity Controls of Multinational Enterprises

Abstract: We use a general equilibrium model to examine the welfare e¡ect of domestic equity requirements on multinational ¢rms in the presence of alternative types of trade instruments and varying degrees of the mobility of foreign capital. It turns out that, under quotas, raising equity requirements improves welfare in the short run but reduces welfare in the long run. In contrast, when tari¡s are in place, the policy of domestic equity requirements lowers welfare in the short run but raises welfare in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It has also been argued that by forcing IJVs, a host government can alleviate informational constraints (Karabay 2010) or promote technology spillovers by inducing technology transfer (Mattoo, Olarreaga, and Saggi 2004). Elsewhere, using a general equilibrium model, Chao and Yu (2000) show that under quotas ( resp . under tariffs), raising LERs improves ( resp .…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has also been argued that by forcing IJVs, a host government can alleviate informational constraints (Karabay 2010) or promote technology spillovers by inducing technology transfer (Mattoo, Olarreaga, and Saggi 2004). Elsewhere, using a general equilibrium model, Chao and Yu (2000) show that under quotas ( resp . under tariffs), raising LERs improves ( resp .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Very different policy recommendations on domestic equity requirements are required for example, depending on whether imports are restricted by tariffs or by quotas, and depending on the degree of capital mobility. Using a general equilibrium model, Chao and Yu (2000) demonstrated that with quotas, increasing the equity requirements improved welfare in the short run but reduced it in the long run. Conversely, with tariffs, domestic equity requirements lower welfare initially but raise it over the long term.…”
Section: The Trade Regime and Sectoral Considerationsmentioning
confidence: 99%
“…Marjit and Mukherjee (1998) considered various types of contractual arrangements with equity participation by a multinational that dominate pure technology collaboration agreements and established that in the presence of a difference between actual and perceived payoffs, foreign equity participation is necessary. Chao and Yu (2000) demonstrated that when tariffs are in place, a policy of domestic equity requirements lowers welfare in the short run but raises welfare in the long run, and the reverse holds under quotas. Marjit and Mukherjee (2001) showed that technological collaboration coupled with foreign equity participation improves the quality of transacted technology relative to pure technology licensing.…”
Section: Introductionmentioning
confidence: 99%